Moderate-intensity exercise affects perceived hunger and fullness but not appetite-related hormones in late pregnancy - Guelfi, K.; Halse, Rhiannon (N R C Research Press, 2013)
The effect of exercise on appetite and appetite-related hormones during pregnancy is not known. This study found that 30 min of moderate-intensity stationary cycling transiently attenuated hunger and increased fullness in late gestational women (n = 12). Exercise did not affect perceived appetite or appetite-related hormones in response to subsequent caloric consumption. These observations suggest that appetite responses do not intrinsically compensate for the additional energy expenditure induced by exercise, at least in the short term.